Elements of applying the principle of proportionality in cyber attacks - Mohammed Abdulkarim Salem; George Armoni (International Journal of Law Research and Studies, 2025)
The principle of proportionality in cyberattacks is a legal and ethical framework that aims to balance the legitimate military impact with the potential damage to civilians and vital civilian objects. This principle is based on reducing the use of electronic force as a new force within cyberspace, to prevent unnecessary or excessive effects, and includes assessing indirect consequences such as disrupting vital infrastructure or basic services. Its application requires an accurate and real assessment of the effectiveness of the attack carried out by the military force against the risks resulting from it, and the adoption of reserve measures to minimise the damage resulting from it, which have a profound impact on civilians and vital infrastructure, in order to preserve international legitimacy and enhance legal and moral responsibility in cyberspace, which, as we know, is a new space of a new nature, so it is very important to apply the principle of proportionality accurately to cyber-attacks.